1986
DOI: 10.1159/000118301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Six Weeks’ Neuroleptic Treatment on the Pituitary-Thyroid Axis in Schizophrenic Patients

Abstract: In order to investigate (a) the effects of 6 weeks’ neuroleptic treatment on the pituitary-thyroid axis in 25 male schizophrenic patients, and (b) the diurnal variation in the thyrotropin (TSH) and prolactin (PRL) responses to thyrotropin-releasing hormone (TRH) in these patients, the TRH stimulation test was performed in each of them at 14.00 and 24.00 h of the same day, both before and after 6 weeks’ treatment with neuroleptics (chlorpromazine or fluspirilene). Also, serum thyroxine (T4), in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several studies, cited as follows, have reported thyroid hormone level abnormalities in hospitalized schizophrenic patients, but, in most cases, patients remain clinically euthyroid. Elevated and normal total T 4 levels have been reported in drug naive and acute schizophrenic patients and are described to normalize or decrease, respectively, as a response to treatment with different drugs (Baumgartner et al, 2000;Kelly and Conley, 2005;Martinos et al, 1986;Rao et al, 1984;Rinieris et al, 1980). Other studies reported a positive correlation between circulating free T 4 and free T 3 with severity of disease (Sim et al, 2002).…”
Section: Thyroid Hormones Retinoids and Schizophreniamentioning
confidence: 99%
“…Several studies, cited as follows, have reported thyroid hormone level abnormalities in hospitalized schizophrenic patients, but, in most cases, patients remain clinically euthyroid. Elevated and normal total T 4 levels have been reported in drug naive and acute schizophrenic patients and are described to normalize or decrease, respectively, as a response to treatment with different drugs (Baumgartner et al, 2000;Kelly and Conley, 2005;Martinos et al, 1986;Rao et al, 1984;Rinieris et al, 1980). Other studies reported a positive correlation between circulating free T 4 and free T 3 with severity of disease (Sim et al, 2002).…”
Section: Thyroid Hormones Retinoids and Schizophreniamentioning
confidence: 99%
“…Rao et al [13] concluded that increased dopaminergic activity affects pituitary secretory functions and may lead to reduced TSH levels. Subclinical hypothyroidism may be present in treatment-naive patients with schizophrenia and treatment with antipsychotics may increase basal TSH levels [14], while Rao et al [15] found no difference between treated and untreated patients. Higher basal TSH levels may be associated with a poorer treatment response in schizophrenia [16], while T4 levels showed a positive correlation with the severity of illness and the degree of clinical response to neuroleptic treatment [17].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with neuroleptics in schizophrenics has been shown to result in lower FT4 I values as well as higher basal TSH and TSH response to TRH, indicating development of hypothyroidism in these patients. 310 Phenothiazines (chlorpromazine, thioridazine, or trifluoperazine) have been found to result in low T 4 levels with normal or increased T 3 levels without other changes in thyroid indices. The cause of these changes may be secondary to decreased synthesis of thyroid hormone or modulation of deiodinase enzymes.…”
Section: Desipraminementioning
confidence: 99%